Genetic and expression analysis of SNPs in the human deoxyribonuclease II: SNPs in the promoter region reduce its in vivo activity through decreased promoter activity - Kimura-Kataoka, Kaori; Yasuda, Toshihiro; Fujihara, Junko; Toga, Tomoko; Ono, Rei-Ichiro; Otsuka, Yosuke; Ueki, Misuzu; Iida, Reiko; Sano, Rie; Nakajima, Tamiko; Kominato, Yoshihiko; Kato, Hideaki; et al. (Electrophoresis, 2012)
Five SNPs in the human DNase II gene have been reported to be associated with rheumatoid arthritis (RA). Genotype and haplotype analysis of 14 SNPs, nine SNPs of which reported in the NCBI dbSNP database in addition to these five SNPs, was performed in healthy subjects. The enzymatic activities of the amino acid substituted DNase II corresponding to each SNP and serum DNase II in healthy Japanese, and promoter activities derived from each haplotype of the RA‐related SNPs were measured. Significant correlations between genotype in each RA‐related SNP and enzymatic activity levels were found; alleles associated with RA exhibited a reduction in serum DNase II activity. Furthermore, the promoter activities of each reporter construct corresponding to predominant haplotypes in three SNPs in the promoter region of the gene exhibited significant correlation with levels of serum DNase II activity. These findings indicate these three SNPs could alter the promoter activity of DNASE2, leading to a decline in DNase II activity in the serum through gene expression. Since the three SNPs in the promoter region of the DNase II gene could affect in vivo DNase II activity through reduction of the promoter activity, it is feasible to identify these SNPs susceptible to RA.